Effects of Fospropofol Disodium and Propofol on the Postoperative Recovery of Elderly Patients Who Underwent Total Hip Arthroplasty: A Retrospective Study - Ding S; Wang Z; Li C; Wang G; Li J; Zhu H; He K (Drug Design, Development and Therapy)
Sheng Ding,1,2 Zaibao Wang,1,2 Chunliu Li,1,2 Guizhi Wang,1,2 Juan Li,1 Hongrui Zhu,2 Keqiang He1,2 1Graduate School of Bengbu Medical University, Bengbu, People’s Republic of China; 2Department of Anesthesiology, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, People’s Republic of ChinaCorrespondence: Keqiang He, Email doctorhector@ustc.edu.cn Hongrui Zhu, Email zhuhongrui@mail.ustc.edu.cnPurpose: Propofol is widely used for general anesthesia in elderly patients. Fospropofol disodium, a precursor of propofol, may reduce the incidence of postoperative nausea and vomiting (PONV). However, the effects of these two drugs on patients’ postoperative recovery quality are unclear. The present study aimed to evaluate the effects of the two drugs on postoperative recovery quality in elderly patients who underwent total hip arthroplasty.Patients and Methods: We retrospectively analyzed 168 patients from the First Affiliated Hospital of USTC from October 2022 to June 2024. These individuals were assigned to fospropofol disodium group (F) or propofol group (P) according to the patients’ anesthesia induction and maintenance medication. The primary outcome was the rate of occurrence of PONV. The secondary outcomes included the time of extubation and the time of stay in post-anesthesia care unit (PACU), hospital length of stay, perioperative hemodynamic data and patients’ liver and renal functions.Results: PONV occurred to be lesser in group F than in group P (15.94% vs 33.33%, P < 0.05). Group P spent less in the extubation time (25.71 vs 33.36 min, P < 0.05) and PACU stay length (62.61 vs 65.65 min, P > 0.05), but hospital length of stay is longer (6.24 vs 5.8 days, P > 0.05). Liver and renal functions indexes and hemodynamic data between the 2 groups were similar (P > 0.05). The type of drug was a factor affecting the time of extubation. The type of drug and the patient’s gender were influential factors in the incidence of PONV.Conclusion: Fospropofol disodium reduces the incidence of PONV in patients. And the effects of fospropofol disodium on postoperative recovery quality are similar to that of propofol in older patients who underwent total hip arthroplasty.Keywords: fospropofol disodium, propofol, total hip arthroplasty, recovery quality